Identification of viral and bacterial etiologic agents of the Pertussis-like syndrome in children under 5 years old hospitalized - Saiki Macedo, Stephanie Alejandra (2018)
Objective: To study the presence of 8 respiratory viruses (Influenza-A, Influenza-B, RSV-A, RSV-B, Adenovirus, Parainfluenza-1, Parainfluenza-2 and Parainfluenza-3) and atypical bacteria (Mycoplasma pneumonia and Chlamydia pneumonia) in samples from Peruvian children under 5 years-old previously analyzed for Bordetella. Pertussis. Methods: A secondary data analysis was performed from a previous cross-sectional study conducted in children with a probable diagnosis of Pertussis from January 2010 to July 2012. All samples were analyzed via Polymerase Chain Reaction (PCR) for the following etiologies: Influenza-A, Influenza-B, RSV-A, RSV-B, Adenovirus, Parainfluenza 1 virus, Parainfluenza 2 virus, Parainfluenza 3 virus, Mycoplasma pneumoniae and Chlamydia pneumoniae. Results: A total of 288 patients were included. The most common pathogen isolated was Adenovirus (49%), followed by Bordetella pertussis (41%) from our previous investigation; the most prevalent microorganisms were Mycoplasma pneumonia (26%) and Influenza-B (19.8%). Coinfections were reported in 58% of samples and the most common association was found between B. pertussis and Adenovirus (12.2%). Conclusions: There was a high prevalence of Adenovirus, Mycoplasma pneumoniae and other etiologies in patients with a probable diagnosis of pertussis. Despite the presence of persistent cough lasting at least two weeks and other clinical characteristics highly suspicious of pertussis, secondary etiologies should be considered in children under 5 years-old in order to give a proper treatment.